Conceptualization and Models of Muslim Counseling in Ghana - Adjeiwa Akosua Affram; Annabella Osei-Tutu (Journal of Muslim Mental Health)
Ghana is a secular state in which Islam is the second largest religion. Counselors who follow principles in Islam and Muslim culture, comprising imams and followers, serve as de facto mental health providers, but their counseling practices have received limited research attention. This study examined the conceptualizations and counseling practices of 19 Muslim counselors aged 32–72 (M=57.83; SD=12.95) who follow principles in Islam and Muslim culture in southern Ghana. Qualitative data was obtained using one-on-one verbal interviews. Data was inductively and thematically analyzed. Results were organized around five main areas: (1) counseling inventory, (2) conceptualizations of counseling, (3) counseling models, (4) process considerations, and (5) personal prescriptions. Participants conceptualized counseling primarily as advising. They provided services in nine different languages and utilized advising and mediatorial models of counseling. The counselors attended to religious considerations and socio-gender norms in their counseling. The study fills important gaps in Muslim mental health research. Implications for professional psychology training and practice, as well as mental health research and advocacy, have been discussed.